Whisper to the blood - Stabenow, Dana (New York : Minotaur Books, 2009)
Between two suspicious murders and a series of attacks on snow mobilers up the Kanuyaq River, part-time P.I. and newly elected chairman of the Niniltna Native Association Kate Shugak has her hands full.
Keywords: Shugak, Kate (Fictitious character); Women private investigators -- Alaska; Murder -- Investigation; Alaska; Mystery fiction